HUBUNGAN FREKUENSI PEMBERIAN ASI DENGAN KEJADIAN IKTERUS NEONATORUM DI RUMAH SAKIT UMUM DAERAH PROVINSI NTB - Nurlathifah N. Yusuf (Yayasan Pendidikan Medika Indonesia, 2021)
Neonatal jaundice is a clinical condition in the form of yellow staining that appears on the sclera and skin due to the accumulation of indirect bilirubin in the blood. Based on preliminary studies that have been conducted at the Regional General Hospital of NTB Province, it shows that in 2017 the number of infants experiencing jaundice was 71 people while in 2018 there were 100 people experiencing jaundice. The purpose of this study was to determine the relationship between the frequency of breastfeeding and the incidence of jaundice in the NTB Provincial General Hospital. This research is an analytic survey research with cross sectional design. The number of samples in the study were 30 people. Data collection through questionnaires. The results showed that of the 30 mothers studied, more frequency of breastfeeding was included in the frequent category (12 x daily) as many as 19 people (63.6%), the majority had jaundice as many as 16 people (53.3%) and there were the relationship between the frequency of breastfeeding with the incidence of jaundice in the NTB Provincial General Hospital with a p value of 0,000 <0.05. In conclusion the higher the frequency of breastfeeding in newborns, the risk of jaundice will be smaller